Preparation and Microwave Absorption Properties of NixSy/PVDF Nanocomposites - Du, Yu-Hui; Gao, Na; Li, Mao-Dong; Wang, Lei; Wang, Guang-Sheng (Frontiers in Materials, 2020)
Octahedral NixSy nanoparticles and NixSy/PVDF nanocomposites are successfully prepared by solvothermal method. The electromagnetic absorption performance of NixSy/PVDF with different filler content is investigated in the range of 2–18 GHz. An optimal reflection loss value of −32.75 dB at 10.48 GHz is achieved for the filler content of 20 wt%, and the bandwidth <−10 dB can reach up to 4.48 GHz with a thickness of 3 mm. Furthermore, fundamental mechanisms of electromagnetic absorbing is discussed, indicating that the interface polarization, electric dipole polarization, Debye relaxation and impedance matching are the main factors affecting the absorption performance of NixSy/PVDF composites.